DISTRIBUTION AND INTENSITY OF MUSCULOSKELETAL PAIN AMONG RECREATIONAL DEADLIFT USERS IN PALEMBANG: A CROSS-SECTIONAL STUDY - Wardiansah Wardiansah; Indri Seta Septadina; Tri Suciati; Ricky Fajar Adipputra (Jurnal Kedokteran dan Kesehatan)
Deadlift is a resistance training exercise commonly used to enhance muscle strength, but improper technique can increase the risk of musculoskeletal pain. This study aimed to analyze the distribution and intensity of musculoskeletal pain in recreational deadlift users using a cross-sectional design. A total of 42 respondents from two gym communities in Palembang were selected through purposive sampling. Data were collected via questionnaires and analyzed descriptively. The results showed that 48.9% of respondents had poor posture during deadlift, and the majority (66.7%) lifted heavy loads (≥70% of 1RM). Musculoskeletal pain was most frequently reported in the lower back (85.3%), followed by the glutes (8.8%) and the right shoulder (5.9%). Most respondents experienced mild pain (37.8%) or no pain at all (37.8%), while moderate pain was reported by 24.4% of respondents. No cases of severe pain were recorded. These findings indicate that although deadlift can cause musculoskeletal discomfort, the pain intensity is generally tolerable.